MELAYU DALAM TANTANGAN GLOBALISASI: Refleksi Sejarah dan Berubahnya Sistem Referensi Budaya - Sunandar, Sunandar (The Pontianak State Institute of Islamic Studies, 2015)
Malay is not just ethnic or tribal entities contained in the archipelago, but Malay is a reflection of unity between Islamic values and community locality contained in it, a person can not be called a Malay if he abandoned Islam in self and life. The participation of Islam in the Malay life seen in the traditions that live in the community, such as AntarAjong in Sambas. In the latest development, Malay traditions faced with the global challenges, force it adapt with the times. This article seeks to uncover the Malay culture in the early days of the development of Islam in the archipelago, see AntarAjong tradition as a traditional reference system and some aspects that lead to changes in traditional references.